Prevalence and Risk Factors for Diabetes Mellitus in A State in South East Nigeria: Results of a Population Based House to House Survey - Ezeani, Ignatius U.; Chukwuonye, Innocent I.; Onyeonoro, Ugochukwu U.; Chuku, Abali; Ogah, Okechukwu S. (Current Diabetes Reviews, 2020)
Background: Population based studies on diabetes mellitus (DM) are scarce in Nigeria. Introduction: This was a population-based house to house survey aimed at determining the prevalence of DM and assessing the risk factors associated with DM in a state in Southeast Nigeria. Methods: This was a cross-sectional observational study in which 1680 adults were recruited using a multistage sampling method to randomly select not more than two suitable participants of both sex in each household from four enumeration areas (EAs) in each local government area (LGA) and the three senatorial zones in the state. A modified World Health Organization (WHO) Stepwise Approach to Surveillance questionnaire was used for data collection and random blood glucose (RBG) was measured after anthropometric assessment. Test statistics used were chi-square, t-test, and logistic regression. Results: The overall prevalence of DM in this study was 3.3%. A positive family history of DM was significantly higher in patients with diabetes: 18.2% vs. 9.6% (p=0.036). The mean (SD) of weight, body mass index (BMI), hip circumference (HC) and waist circumference (WC) were significantly higher in patients with DM(p=0.001,<0.001,<0.001,<0.001, respectively).The odd ratio (95% CI) of a person>35years developing DM was 3.89(1.11-13.60). The OR (95% CI) for waist-hip ratio (WHR) was 3.04 (1.02-9.03) and family history of DM had an OR of 2.62(0.88-6.50). The odd of developing DM is positively associated with age>35years, increased WHR, WC, family history of DM, BMI>25Kg/m2, and HC. The odd of developing DM was negatively associated with smoking. Conclusion: The prevalence of DM in this study was 3.3%. A BMI>25 kg/m2, WHR >0.85, family history of DM, HC, and older age were associated with significantly higher prevalence.
Keywords: Diabetes mellitus